A general approach to Bayesian portfolio optimization - Alexander Bade; Gabriel Frahm; Uwe Jaekel (University of Cologne, Seminar of Economic and Social Statistics, 2008)
We develop a general approach to portfolio optimization taking account of estimation risk and stylized facts of empirical finance. This is done within a Bayesian framework. The approximation of the posterior distribution of the unknown model parameters is based on a parallel tempering algorithm. The portfolio optimization is done using the first two moments of the predictive discrete asset return distribution. For illustration purposes we apply our method to empirical stock market data where daily asset logreturns are assumed to follow an orthogonal MGARCH process with t-distributed perturbations. Our results are compared with other portfolios suggested by popular optimization strategies.
Keywords: 330; Bayesian portfolio optimization; Gordin's condition; Markov chain Monte Carlo; Stylized facts